Augmented Reality Animasi Surat Pendek Al-Quran Berbasis Android - riyadi, Virgy andrean; ulum, Muhamad Bahrul (PT. Publikasiku Academic Solution, 2025)
The development of technology has significantly impacted various fields, including education. One of the emerging technologies, Augmented Reality (AR), provides interactive and engaging learning experiences. This research focuses on the design and development of an Android-based application that utilizes AR technology to animate short Quranic surahs (Juz Amma) for children at Taman Pendidikan Al-Qur'an (TPQ). The application aims to make Quranic learning more engaging, interactive, and effective for young learners by integrating AR with traditional Quranic teaching methods. The research methodology includes the identification of problems, literature review, data collection through observation, interviews, and library study, as well as the design and development of the AR-based learning application. The findings demonstrate that AR can enhance children's engagement and retention in learning short surahs, making the Quran more accessible and enjoyable for younger audiences. This innovative approach is expected to offer a solution to the challenges faced in Quranic education today.